Response of the interface between the ball and the raceway of rolling bearing under starved lubrication. Issue 5 (January 2021) - Bian, Z; Song, C; Meng, L H; Zhou, Q H
Abstract: The interface state of the rolling bearing contact pair often directly determined the service performance of the bearing for the aviation equipment, the ball-raceway contact interface would develop from the homogeneous lubrication to starved lubrication when used for a while, the plasto-elastohydrodanamic lubrication analysis model was used to describe the ball-raceway contact interface lubrication condition. The influence of the normal pressure, the rolling speed and the service time to the ball-raceway contact interface wear behavior was investigated by the gearbox and rolling bearing on condition of starved lubrication, it was found that the centre region of the raceway generated concave residual deformation, while the convex residual deformation occurred at the lubrication region's edge and its surrounding region, the groove and scratch marks were emerged on the contact surface of ball and raceway, which were accelerated produced by the normal load and rolling speed of rolling bearing, besides that the ball-raceway contact interface assumed adhesive wear behavior and the wear width became gradually larger over the time.